Clinical and Laboratory Predictors associated with Complicated Scrub Typhus - Kim, Mi-Hee (Infect Chemother, 2019)
BACKGROUND: Scrub typhus, a mite-borne disease caused by bites of Orientia tsutsugamushi-infected chiggers, is endemic in Asia-Pacific countries. In Korea, it is a seasonal disease prevalent in autumn and one of the important causes of acute undifferentiated febrile illness. The purpose of this study was to identify the risk factors for the prediction of the severe clinical course of scrub typhus and to investigate the differences in the clinical and laboratory findings of hospitalized elderly and non-elderly patients with scrub typhus. MATERIALS AND METHODS: This study retrospectively reviewed the medical records of patients diagnosed with scrub typhus. RESULTS: A total of 710 patients were enrolled and 43.9% of them were elderly patients. The number of patients with complicated scrub typhus was 168 (23.7%) and the most common complication of severe scrub typhus was hepatic dysfunction (10.7%) followed by pneumonia (7.2%), acute kidney injury (4.9%) and shock (2.4%). Blood urea nitrogen ≥20 mg/dL, adenosine deaminase (ADA) ≥100 IU/L, pulmonary edema or pleural effusion, lactate dehydrogenase ≥500 U/L, alkaline phosphatase ≥400 IU/L, ferritin ≥500 ng/mL and absence of skin rash were independently associated with severe scrub typhus. There was no significant difference in the incidence of complicated scrub typhus between elderly and non-elderly patients. Absence of skin rash, pulmonary edema, pleural effusion, serum creatinine ≥1.5 mg/dL, total bilirubin ≥1.5 mg/dL, ADA ≥100 IU/L and ferritin ≥500 ng/mL were significantly associated with a longer hospitalization (≥10 days). CONCLUSION: The several independent predictors of complicated scrub typhus were identified in this study. Absence of skin rash, the increased levels of serum ADA and ferritin were identified as the predictors of complicated scrub typhus, which were also associated with a prolonged hospitalization.